MACROFUNGI DIVERSITY IN MOUNT BURNI TELONG BENER MERIAH REGENCY ACEH PROVINCE - Siti Nurchalidah; Zulfan Arico; Fitriani Fitriani (BIOLINK (Jurnal Biologi Lingkungan Industri Kesehatan), 2021)
Mount Burni Telong has a diversity of fungi that play an important role in the forest ecosystem. This study aimed to determine the types of macrofungi found in Mount Burni Telong and index diversity macrofungi found in Mount Burni Telong. The method used in this study was to use the pathway method by observing macrofungi along the hiking trail with a distance of 10 meters to the left and 10 meters to the right starting from an altitude of 1800 mdpl to an altitude of 2600 mdpl. Macroscopic fungi found were to identified and measured the physico-chemical parameters of the environment. Macroscopic fungi found were dominated by the Basidiomycota division and the Polyporaceae family. The results obtained were 31 macroscopic fungi from 2 divisions, 6 classes, 6 orders, 21 families, 26 genera, and 31 species. The most macroscopic fungi found in the Basidiomycota division, Agaricomycetes class, were 23 species and at least in the Ascomycota division, Pezizomycetes class, was as many as 1 species.